Gambaran Dukungan Keluarga Terhadap Perawatan Paliatif Pada Pasien Yang Menjalani Hemodialisis Di RSMH Palembang - Hanifati Akalili; Dhona Andhini; Nurna Ningsih (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Family support is a positive influence given by family members to other family members. Family support is needed because the family plays an important role in the stage of patient health care and has a good impact on the patient. Family support can be in the form of an attitude, an act of family acceptance that can be in the form of emotional support and hope (attention, affection), real support (valuing, feedback), information support (advice, advice, information) as well as in the form of real support (energy assistance, funds and time). This study aims to determine the picture of family support for palliative care in patients undergoing hemodialysis at RSMH Palembang. This type of research is quantitative with a population of 149 people. Purposive sampling, with a total sample of 60 patients with chronic kidney failure who underwent hemodialysis at RSMH Palembang. Univariate research results showed respondents with emotional support and good expectations there were 54 people (90%) and less than 6 people (10%), real good support there were 59 people (98.3%) and those lacking 1 person ( 1.7%), and all information support is good namely 60 people (100%). Further research needs to be carried out research with deeper and more complete methods, namely qualitative methods, because with qualitative methods researchers can obtain information and study family support more deeply